2006
DOI: 10.2109/jcersj.114.995
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation, Microstructure and Crystallography of Dense NaNbO<sub>3</sub> Ceramics with Ultra-Fine Grain Size

Abstract: Paper péÉÅá~ä fëëìÉ Äó dìÉëí bÇáíçêë aÉÇáÅ~íÉÇ íç mêçÑK d äìåíÉê mÉíòçïW jçÇÉêå qêÉåÇë áå^Çî~åÅÉÇ`Éê~ãáÅë çåëçäáÇ~íáçå, jáÅêçëíêìÅíìêÉ~åÇ`êóëí~ääçÖê~éÜó çÑ aÉåëÉ k~kÄl P Éê~ãáÅë ïáíÜ räíê~cáåÉ dê~áå páòÉ The present study reports on the preparation and structural characterization of dense NaNbO 3 ceramics with ultrafine grain size. Nanocrystalline raw powders obtained via microemulsion mediated synthesis were consolidated to green compacts, sinterforged to ceramic pellets with high density and ultra-fine micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The powder was then washed with acetic acid solution to remove the residual BaCO 3 and the unreacted Ba ions in solution. The removal of residual BaCO 3 is crucial because its Raman spectra appear in the range of <200 cm −1 [20]. After washing, the recovered powder was dried at 60 • C on a hot plate for 48 h.…”
Section: Synthesis Of Batio 3 Nanoparticlesmentioning
confidence: 99%
“…The powder was then washed with acetic acid solution to remove the residual BaCO 3 and the unreacted Ba ions in solution. The removal of residual BaCO 3 is crucial because its Raman spectra appear in the range of <200 cm −1 [20]. After washing, the recovered powder was dried at 60 • C on a hot plate for 48 h.…”
Section: Synthesis Of Batio 3 Nanoparticlesmentioning
confidence: 99%
“…[2] Based on a microemulsion approach, very different compounds with defined diameter and chemical composition are within reach. Recent work aiming at nanometer-scale ZnS, [3] LiFePO 4 , [4] AgBr, [5] SrAl 2 O 4 , [6] Fe 3 O 4 , [7] CdMoO 4 , [8] YVO 4 , [9] NiB, [10] BiOCl, [11] MnO 2 , [12] BaTiO 3 , [13] WO 3 , [14] Si, [15] TiO 2 , [16] or NaNbO 3 [17] may elucidate the potential of microemulsions concerning chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been denoted to be a severe drawback of microemulsion techniques. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Another immanent restriction of microemulsion techniques is the limitation to ambient temperature. This is a result of the thermal stability of the micelles, which leads to phase separation at temperatures higher than about 80 8C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing concern about environmental problems has led to the development of lead-free piezoelectric materials with high piezoelectric properties. (K 0:5 Na 0:5 )NbO 3 (KNN), [3][4][5][6][7][8][9][10][11][12] (Bi 0:5 Na 0:5 )TiO 3 (BNT), 10,[13][14][15][16] and BaTiO 3 (BT), [17][18][19] as lead-free piezoelectric materials, have been studied for their good piezoelectric properties. In 2004, Saito et al reported that (Na 0:52 K 0:44 Li 0:04 )(Nb 0:84 Ta 0:10 Sb 0:06 )O 3 (NKLNTS) in the KNN system shows excellent piezoelectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%